Recent Publications (Quarterly Journal of Economics, 1948)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 62, Issue 3, May 1948, Pages 472–474, https://doi.org/10.1093/qje/62.3.472 Published: 01 May 1948